2015
DOI: 10.1111/ppl.12329
|View full text |Cite
|
Sign up to set email alerts
|

Activation of photoprotective winter photoinhibition in plants from different environments: a literature compilation and meta‐analysis

Abstract: Overwintering plants face a pronounced imbalance between light capture and use of that excitation for photosynthesis. In response, plants upregulate thermal dissipation, with concomitant reductions in photochemical efficiency, in a process characterized by a slow recovery upon warming. These sustained depressions of photochemical efficiency are termed winter photoinhibition (WPI) here. WPI has been extensively studied in conifers and in few overwintering crops, but other plant species have received less attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 43 publications
5
39
0
Order By: Relevance
“…Although it is difficult to compare xanthophyll interconversion rates among studies, our (Z+A) dark-retention data (Figs. 3 and 4) from arctic species are in line with similarly collected data from species growing in harsh environments as reported in the meta-analysis by Miguez et al (2015, and their Fig. 2, part b).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although it is difficult to compare xanthophyll interconversion rates among studies, our (Z+A) dark-retention data (Figs. 3 and 4) from arctic species are in line with similarly collected data from species growing in harsh environments as reported in the meta-analysis by Miguez et al (2015, and their Fig. 2, part b).…”
Section: Discussionsupporting
confidence: 89%
“…The majority of field-based studies has been conducted in temperate, semi-arid, and Mediterranean climates, with only limited investigations conducted in the end-members of our global climate system, such as tropical rainforest (Königer et al, 1995;Matsubara et al, 2009;Krause et al, 2012);desert (Barker and Adams, 1997;Barker et al, 2002); boreal forest (Ensminger et al, 2004;Yamazaki et al, 2007;Porcar-Castell et al, 2008; or tundra (this study). Indeed, three recent meta-analyses suggest that total xanthophyll pools and the relative concentration of zeaxanthin are clear indicators of the response of plants to harsh growing conditions or environmental stress (Wujeska et al, 2013;Esteban et al, 2015;Miguez et al, 2015), but these studies lack data reported in more extreme environments, particularly at high latitudes and the tundra biome.…”
Section: Introductionmentioning
confidence: 99%
“…Under severe stress conditions, specially low temperature, the VAZ cycle does not reach a complete relaxation (Demmig-Adams and Adams, 1996; Demmig-Adams et al, 2006), and AZ/VAZ is typically higher than 0.5 before dawn (Míguez et al, 2015). This process has been characterized in detail in boreal conifers and alpine evergreens (Verhoeven, 2014; Míguez et al, 2017) involving profound change in the organization of photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…PsbS-dependent qE can be generated within seconds but the synthesis of zeaxanthin and its reconversion back to violaxanthin in low-light occurs on a timescale of minutes 2224 leading to the suggestion that zeaxanthin persistence is a ‘memory’ of high-light events, enabling a rapid response to a re-occurrence of saturating light 2 . Slower-relaxing components of NPQ include qI or inhibitory quenching which can be formed as a result of damage to PSII and its repair which is a process requiring time, energy and protein synthesis 25,26 or from the more persistent retention of zeaxanthin 27 .…”
Section: Introductionmentioning
confidence: 99%